PECULIARITIES OF THE DEVELOPMENT AND IMPLEMENTATION OF AVIATION BIOFUELS IN UKRAINE - Boichenko, S. V.; Vovk, O. O.; Iakovlieva, A. V.; Boichenko, M. S. (Science-based technologies, 2014)
The modern environmental problems caused by the activity of aviation industry are figured out in the article. The main tendencies for transition to alternative jet fuels all over the world are described. Attention is paid to the policies of developed countries intended to the implementation of biofuels in aviation, and introduction of new standards for alternative jet fuels quality. Contemporary state of jet fuels production and use in Ukraine is discussed. Ukrainian experience in development of national policy for introduction of alternative jet fuels into civil aviation is described. The current problems, which are the barriers nowadays for jet biofuels implementation in Ukraine are presented in details. At the same time benefits that will be achieved in a result of biofuels application are emphasized.